1998
DOI: 10.1103/physrevlett.81.73
|View full text |Cite
|
Sign up to set email alerts
|

Strong Suppression of the Positronium Channel in Double Ionization of Noble Gases by Positron Impact

Abstract: Positron-induced double ionization of helium and neon has been studied at energies from threshold to 900 eV. A remarkable difference between the near-threshold behavior of the single and double ionization cross sections is found: Single ionization is dominated by positronium (Ps) formation, while for double ionization the Ps channel is absent or strongly suppressed. Absolute cross sections for the two targets have been derived and are compared to a modified Rost-Pattard parametrization. Good agreement is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
3
20
1
Order By: Relevance
“…Ps and E r and also the validity of the N 2 factor. The double ionization data for Ne again do not fit quite so well but one should note that the magnitude of σ 2 Ps is very small for this atom and the fractional error is large, the absolute error being of the same order of magnitude as the data points (for clarity, only the error bar at one energy is shown). Equation (1) can be used to predict σ N Ps at energies within the so-called Ore gap (for a definition see [1]) for degrees of ionization which have not yet been measured, or to confirm the validity of experimental results.…”
Section: L670mentioning
confidence: 92%
See 1 more Smart Citation
“…Ps and E r and also the validity of the N 2 factor. The double ionization data for Ne again do not fit quite so well but one should note that the magnitude of σ 2 Ps is very small for this atom and the fractional error is large, the absolute error being of the same order of magnitude as the data points (for clarity, only the error bar at one energy is shown). Equation (1) can be used to predict σ N Ps at energies within the so-called Ore gap (for a definition see [1]) for degrees of ionization which have not yet been measured, or to confirm the validity of experimental results.…”
Section: L670mentioning
confidence: 92%
“…In a recent letter, Humberston and Van Reeth [1] proposed a model of positronium (Ps) formation in positron-atom collisions in which the initial formation process is followed by the possible recapture of the electron in the Ps by the residual ion. This two-stage process, which was initially devised to explain the suppression of Ps formation in the double ionization of helium and neon [2,3], predicts a correlation between the Ps formation cross section, σ Ps , and E r , the energy liberated to the positron when the electron is recaptured. At a given energy slightly in excess of the relevant Ps formation threshold, the experimental values of σ Ps for both double and single ionization of the noble gases were found to be highly correlated with E r , the relationship being of the form,…”
mentioning
confidence: 99%
“…Calculations by Schultz and Olson [13] are well consistent with experimental data for velocities lower than 3 a.u. [8]. But, for the higher velocity, their results fall off more rapidly than the experimental data.…”
Section: B Positron-impacted Ionization Of Heliummentioning
confidence: 82%
“…Charlton [7] measured the double-to-single ratio /?2i of positron-helium impact and electron-helium impact and proposed the assumption that the difference of double ionization between the electron and proton was attributed to their opposite charge. Bluhme [8] found that positronium for mation was strongly suppressed during the double-ionization process. In theory, Basu [9], Baluja HO], Zhifan [11], and Mukherjee [12] used quantum methods to study the ionization cross section of positron-helium scattering.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent papers we have reported on the total double ionization cross sections of helium, neon and xenon by positron impact (Bluhme et al 1998(Bluhme et al , 1999. Our investigations have focused on the near-threshold region.…”
Section: Introductionmentioning
confidence: 99%